Understanding The Use Of Management Techniques Used By Local Information Technology Companies In India To Overcome Multinational Barriers - Abhinav Kumar Das (Digital Repository of Theses, 2024)
In the dynamic landscape of the global information technology (IT) industry, local companies in India face unique challenges when striving to expand their operations beyond national borders. This study delves into the strategic management techniques employed by Indian IT companies to navigate and overcome barriers associated with multinational operations. The research employs a qualitative approach, combining in-depth interviews with key executives, case studies of successful ventures, and a comprehensive review of existing literature. The study identifies key challenges such as cultural differences, regulatory complexities, and diverse market landscapes that Indian IT companies encounter during their international expansion. Through an exploration of successful case studies, the research aims to uncover patterns of management strategies implemented by these companies to not only mitigate these challenges but also leverage them as opportunities for growth. By understanding the specific managerial approaches adopted by Indian IT firms, this research contributes valuable insights into how local enterprises can strategically position themselves in the global IT ecosystem. The findings of this study have implications for both practitioners and policymakers, offering a nuanced understanding of the management techniques that foster success in the internationalization efforts of Indian IT companies. This research contributes to the broader discourse on the globalization of IT enterprises, shedding light on the adaptive strategies that local IT companies in India employ to thrive in an environment traditionally dominated by multinational corporations.